Da sedução malandra à imaginação tática: a sociogênese do pensamento futebolístico brasileiro e sua representação discursiva - Cavalcante, Diego Frank Marques (2010)
This research has its main focus on the investigation of the “soccer thought” in Brazil and its discursive use. Taking as a point of depart fieldwork including semiotic analyses of soccer games, Nelson Rodrigues literature and ethnography of pubs in Ceará. Thought is treated here as creative potential: to invent “football spaces” using the body as the main instrument of expression. On the other hand, discursive appropriation means the representation and the social uses of the performances made by soccer players. The history of the “soccer thought” will be analyzed of the four “social patterns”: of elite, “malandro”, “malandro – disciplined” and “tactics- several function”. The main propose here is to open new ways of understanding the logic of “soccer thought” in its appropriations, emphasizing its body and a discursive uses.